c-MYC mRNA destabilization inhibited lethal pancreatic cancer in vivo with significant survival outcomes - Dorji, Jigme P.; Chen, Queenie; Perera, Sandali G.; Aijaz, Fizza; Li, Petvy; Sania, Tanjina; Matsui, Hiroshi; Awah, Chidiebere U. (Frontiers in Pharmacology, 2025)
Pancreatic ductal carcinoma is the most common and deadly form of pancreatic cancer, with an 11% survival rate. There is currently no cure. The first-line, mainstay therapy for pancreatic cancer is gemcitabine, capecitabine, or FOLFIRINOX. After 21 months, the chemoresistance begins, driven by the oncogenic c-MYC signal. This is a significant clinical and cancer biology challenge. The c-MYC oncogene has been shown to be overexpressed in primary (43.1%) and metastatic (31.6%) pancreatic cancers, respectively, and is the primary driver of the neoplastic changes and progression of pancreatic cancer metastasis. Here, we report the in vivo downregulation and inhibition of metastatic c-MYC-expressing lethal pancreatic cancer by the mRNA drug 3′UTRMYC1-18. The drug achieved on-target, in vivo c-MYC dose-dependent downregulation with complete pathological response, inhibition of liver, lung, and brain metastases with significant survival outcome, is safe, has a stable long half-life, and is well tolerated. Mechanistically, the therapeutic efficacy of the MYC-mRNA drug was achieved through downregulation of c-MYC-PD-L1.